Reassessment of the earliest documented stegosaurian fossils from Asia. (31st December 2016) - Borinder, Niclas H.; Poropat, Stephen F.; Kear, Benjamin P.
Abstract: In 1929, the famous Swedish palaeontologist Carl Wiman documented the first unequivocal stegosaurian dinosaur fossils from Asia. His material comprised an isolated dermal spine, together with a dorsal vertebra that was briefly described but never figured. Since then these remains have languished in obscurity, being noted in some stegosaur review articles but often ignored altogether. However, recent auditing of the Museum of Evolution palaeontological collection at Uppsala University in Sweden has led to the rediscovery of Wiman's original specimens, as well as two additional previously unrecognised stegosaurian dorsal vertebrae. All of these bones derive from the Lower Cretaceous (Berriasian–Valanginian) Mengyin Formation of Shandong Province in eastern China, and are morphologically compatible with the stratigraphically proximal stegosaurian taxon Wuerhosaurus from the Valanginian–Albian Tugulu Group in the Xinjiang Uyghur Autonomous Region of Western China. Wiman's seminal stegosaurian fossils thus expand current palaeobiogeographical distributions, and contribute to the otherwise enigmatic record of Early Cretaceous stegosaurian occurrences globally.